Leukocyte Telomere Length Predicts Progression From Paroxysmal to Persistent Atrial Fibrillation in the Long Term After Catheter Ablation - Wang, Qianhui; Liu, Zheng; Dong, Ying; Yang, Xinchun; Chen, Mulei; Gao, Yuanfeng (Frontiers in Cardiovascular Medicine, 2022)
Backgrounds: Aging is significantly associated with the incidence and progression of atrial fibrillation (AF). This study aimed to evaluate the potential predictive value of leukocyte telomere length (LTL) for progression from paroxysmal AF (PAF) to persistent AF (PsAF) after catheter ablation. Methods and Results: A total of 269 AF patients (154 PAF and 115 persistent AF (PsAF) patients respectively) were prospectively enrolled and all PAF patients at baseline were regularly followed-up to determine whether and when they should progress to PsAF after catheter ablation therapy. Baseline relative LTL was measured by quantitative real-time PCR. There was a significant negative association between LTL and age (r=-0.23, p<0.001). PsAF patients had significantly shorter LTL than those with PAF. After a mean follow-up of 854.9±18.7 days, progression events occurred in 35 out of the 154 PAF patients. Those progressed PAF patients were older (70.9±8.0 vs 62.3±10.3, p<0.001) and had shorter LTL (1.2±0.3 vs 1.5±0.3, p<0.001) than those who did not. Receiver operating characteristic (ROC) curve analysis showed a significant value of LTL in distinguishing PAF patients from PsAF patients, with an area under the ROC curve (AUC) of 0.63 (95% confidence interval (CI) 0.56-0.70, p<0.001), and the optimal cut-off value of LTL was 1.175, with a sensitivity and specificity of 56.03% and 82.04% respectively. All PAF patients were divided into two subgroups according to the optimal cut-off point of LTL calculated by ROC curve analysis: high LTL group (≥1.175) and low LTL group (<1.175). Kaplan-Meier curve analysis showed that PAF patients with shorter LTL had a significantly higher rate of progression after catheter ablation (40.5% vs. 18.8%, log-rank test p<0.001). Multivariate Cox proportional-hazards model indicated that LTL (hazard ratio (HR): 0.12, 95%CI:0.04-0.39, p<0.001) was an independent predictor for progression from PAF to PsAF after catheter ablation therapy, while HATCH scores not (HR:0.97, 95%CI: 0.64-1.48, p=0.888). Conclusion: LTLs were significantly associated with AF types. LTL was independently associated with progression from PAF to PsAF after catheter ablation therapy.